Quasiconvex Semidefinite Minimization Problem. (12th December 2013) - Enkhbat, R.; Bayartugs, T.
Abstract : We introduce so-called semidefinite quasiconvex minimization problem. We derive new global optimality conditions for the above problem. Based on the global optimality conditions, we construct an algorithm which generates a sequence of local minimizers which converge to a global solution.